Dampak Pemberian Semen Gresik UKM Award Terhadap Peningkatan Kinerja UKM Binaan (Study Pada Penerima Award Program CSR PT. Semen Gresik ) - W, A.A Raditya Putr; Ludigdo, Unti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aimed to see whether the impact of the SME Award Semen Gresik may affect the performance of SMEs assisted, especially the SMEs receiving the award. Improved performance here is the improved performance of the economy as well as social and enverimentalÂ happened to SMEs after receiving the award. The SME research center here is a winner in each category of the competition and the overall winner at the event in Semen Gresik SME award. The categories examined are employment, growth in exports and imports, compliance with the installment obligation and entrepreneurship, administration and compliance with best winners (overall winner). This research uses descriptive qualitative method added the assessment ratio in accordance with the conditions of SMEs. Based on the method of research, the entire SMEs that receive the award has increased performance, both in terms of economic or social and environmental. The rise of the economy have different variants of the value generated while the ratio in terms of social and environmental as well as improvements in a positive performance in the contribution of SMEs. Keywords: SMEs, economic, social and environmental performance, and award.